2001
DOI: 10.1097/00006534-200111000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years of Experience with the Submental Flap

Abstract: This article describes the authors' experience with the submental flap over the past 10 years. A brief review of the key points and some refinements in the operative technique are discussed. The results concern 31 patients with a mean age of 57 years. All flaps were pedicled except two. One case of composite flap with bone was used. The mean size of the flap was 11.8 x 5.5 cm, and the mean postoperative stay was 11.1 days. Complications encountered were one case of temporary palsy of the marginal mandibular br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 12 publications
3
64
0
11
Order By: Relevance
“…It is thus defined by the maximum width of the flap which allows the primary closure. The aesthetic outcome is usually very good, which our experience confirms especially for older people where there is significant excess skin and all that remains is an inconspicuous scar of wrinkled skin [6][7][8]. The extent of the flap is also acceptable, reliably serves to cover defects in tongue and/tongue floor, floor of the mouth, face, and soft and hard palate.…”
Section: Discussionsupporting
confidence: 55%
“…It is thus defined by the maximum width of the flap which allows the primary closure. The aesthetic outcome is usually very good, which our experience confirms especially for older people where there is significant excess skin and all that remains is an inconspicuous scar of wrinkled skin [6][7][8]. The extent of the flap is also acceptable, reliably serves to cover defects in tongue and/tongue floor, floor of the mouth, face, and soft and hard palate.…”
Section: Discussionsupporting
confidence: 55%
“…The same was true for our measurements from a point just anterior to the facial artery. We therefore suggest, as has been alluded to in the clinical literature (Bron and O'Brien, 1997;Baker and Conley, 1979;Pistre et al, 2001), that the MMB can be found significantly inferior to the inferior border of the mandible.…”
Section: Discussionmentioning
confidence: 53%
“…Alteration of the position of the nerve during dissection may play a minor role in this variation because extreme caution was taken not to disturb the position of the nerve during the dissection. Furthermore, the variation in the position of the MMB to the inferior border of the mandible, has been widely reported in the clinical literature (Bron and O'Brien, 1997;Baker and Conley, 1979;Pistre, 2001). This fact actually makes this nerve so vulnerable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone and soft tissue defects after gunshot trauma have been managed by different multistage reconstructions [3,4]. Pistre et al [5] emphasized that large facial defects must be repaired by a flap suitably matched with the contour, color, and tissue texture of the face. The cervicopectoral rotation flap has been used in facial reconstruction after cancer surgery [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%